2018
DOI: 10.1073/pnas.1715225115
|View full text |Cite
|
Sign up to set email alerts
|

Circadian clock-dependent and -independent posttranscriptional regulation underlies temporal mRNA accumulation in mouse liver

Abstract: SignificanceRhythms in gene expression propelled by the circadian clock and environmental signals are ubiquitous across cells and tissues. In particular, in mouse tissues, thousands of transcripts show oscillations with a period of 24 hours. Keys question are how such rhythms propagate and eventually exert functions, but also how these are generated. Here, we developed a mathematical model based on total RNA-seq to classify genes according to the respective contributions of transcriptional and posttranscriptio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 61 publications
14
69
0
Order By: Relevance
“…This coherent shift most likely represents a cell-cycle defect in the few hepatocytes that underwent through mitosis during the course of the experiment in order to maintain liver homeostasis, as knockdown of condensin II has been shown to lead to extended prometaphase (Green et al, 2012). Most of the other mis-regulated genes have been shown to exhibit a circadian pattern of expression (Fang et al, 2014;Wang et al, 2018). The predominance of circadian genes (defined as gene showing an expression profile varying with at least a 2-fold amplitude during a 24-h period) is highly significant (two-tailed Chi-square test with Yates' correction, P<0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This coherent shift most likely represents a cell-cycle defect in the few hepatocytes that underwent through mitosis during the course of the experiment in order to maintain liver homeostasis, as knockdown of condensin II has been shown to lead to extended prometaphase (Green et al, 2012). Most of the other mis-regulated genes have been shown to exhibit a circadian pattern of expression (Fang et al, 2014;Wang et al, 2018). The predominance of circadian genes (defined as gene showing an expression profile varying with at least a 2-fold amplitude during a 24-h period) is highly significant (two-tailed Chi-square test with Yates' correction, P<0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…Peak time and amplitude of circadian variation were taken fromWang et al 2018. Cell cycle data was obtained from Cyclebase v3(Santos et al 2015) Molecular and cellular processes identified by GO-term enrichment analysis.…”
mentioning
confidence: 99%
“…First, could deadenylation help bridge the circadian rhythm with other rhythmicity? For example, genes related to poly(A) tail regulation, such as Parn, one of the rhythmically expressed deadenylases, are suggested to gain rhythmicity from clock-independent signals (Wang, Symul et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While rhythmic transcriptional control has been extensively studied, rhythmic control of gene expression also occurs beyond the transcription process (Kojima, Shingle et al 2011, Hirano, Fu et al 2016, Gobet and Naef 2017. Recent genome-wide analyses and mathematical modeling particularly highlighted the role of post-transcriptional regulations in driving rhythmic mRNA expressions , Menet, Rodriguez et al 2012, Luck, Thurley et al 2014, Trott and Menet 2018, Wang, Symul et al 2018. Post-transcriptional regulation targets various processes, such as RNA splicing, nuclear export, cellular translocation, dormancy and degradation of mRNA (Keene 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Further, the observed oscillations in NOCT mRNA level necessitate control of mRNA decay in addition to the aforementioned transcriptional control. Indeed, a recent study indicated that NOCT mRNA levels may be regulated by both rhythmic transcription and degradation in mouse liver [80]. Thus far only the liver-specific microRNA miR-122 has been shown to fine-tune the NOCT mRNA abundance profile in mouse liver [81].…”
Section: Noct Expression and Biological Functionsmentioning
confidence: 99%